ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN MODA TRANSPORTASI UDARA PADA MASYARAKAT KAB. KAPUAS HULU KALIMANTAN BARAT - Tuti Susilawati (ADISAM PUBLISHER, 2024)
In a region, transportation is one of the keys to the economic activities of a community and the development of a region. In Kapuas Hulu Regency itself there are already various modes of transportation available with their respective advantages and disadvantages, one of which is air transportation. the use of air transportation in the Kapuas Hulu Regency area is very minimal because people prefer to use land transportation. This research uses a mix method approach and analysis using the AHP (Analytical Hierarchy Process) method. Based on the calculation results obtained CR value of 0.00769, it is considered consistent and means that the above calculations have been declared correct. From the four demographics, namely gender, age, occupation and income, it is concluded that men aged 19-24 years and working as students with an income of Rp. 1,000,000-Rp.3,000,000 are the dominant passengers at Pangsuma Putussibau Airport. The most influential factors are cost, second wake travel, third travel destination, fourth security and last comfort.